Implementasi Kebijakan Penanggulangan Tuberkulosis di Provinsi Kepulauan Riau - Karina Gladis Panggabean; Novi Winarti (Dinasti Review, 2024)
: In Presidential Decree Number 67 of 2021, Indonesia has a national target and strategy for Tuberculosis Elimination. This research aims to analyze how the Tuberculosis control policy is implemented in the Riau Islands Province. This research uses a qualitative descriptive research method where the data obtained is expressed in written form and described (described) according to field facts, both primary data and secondary data. With data collection techniques through interviews and documentation. The results of the research show that although the achievements in finding and treating cases of Tuberculosis and unexpected Tuberculosis from each district or city in the Riau Islands province are still far from the target and there are still challenges in implementing the programs contained in this policy. However, looking at the 7 implementation indicators according to Ripley, namely Access, Coverage, Frequency, Bias, Service Accuracy, Accountability, Program Suitability to Needs, the implementation of the Tuberculosis Control policy in the Riau Islands province has been running in accordance with these indicators. Every policy implemented by the implementers is also implemented in accordance with applicable regulations and in accordance with the respective standard operating procedures (SOP) of each implementing agency involved.